Face-Specific Pupil Contagion in Infants - Tsuji, Yuki; Kanazawa, So; Yamaguchi, Masami K. (Frontiers in Psychology, 2022)
Pupil contagion is the phenomenon in which an observer’s pupil-diameter changes in response to another person’s pupil. Even chimpanzees and infants in early-development stages show pupil contagion. This study investigated whether dynamic changes in pupil diameter would induce changes in infants’ pupil diameter. We also investigated pupil contagion in the context of different faces. We measured the pupil-diameter of 50 five- to six-month-old infants in response to changes in the pupil diameter (dilating/constricting) of upright and inverted faces. The results showed that 1) in the upright presentation condition, dilating the pupil diameter induced a change in the infants’ pupil diameter while constricting the pupil diameter did not induce a change, and 2) pupil contagion occurred only in the upright face presentation, and not in the inverted face presentation. These results indicate the face-inversion effect in infants’ pupil contagion.